The Burley manuscript - Redford, Peter (Manchester Spenser., 2017)
"The Burley manuscript is a miscellany compiled in the late sixteenth and early seventeenth century, unique in size and variety. In this study, annotated transcriptions are given of all of the private letters in English and all the English verse. Incipit transcriptions and identification are provided for each of the other items, including those in foreign languages. The history and provenance of the collection are described in detail, with lengthy notes on memorial transcription of verse and prose, and the clandestine interception of letters. The book makes available texts, annotations and commentary that will have an impact on a wide range of scholarship. It will be found useful to literary scholars, editors, and social historians, illuminating such diverse subjects as the circulation of verse, the correspondence of John Donne, the self-fashioning of English gentlemen after the classical Romans of their class and the government's paranoiac spying on its own citizens."--Publisher's description